The refreshing course program and an introspective survey on occupational health efforts for informal industry in the catchment areas of Srandakan Public Health Center in Bantul: a case report - Noor Alia Susianti; Fifi Sumarwati; Budi Setyowati; Suhandriyah Suhandriyah (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Purpose: Srandakan sub-district as one of the sub-district in Bantul which has a lot of informal industry that caused a lot of work-related accidents and health problems. These problems can be prevented. One of the prevention is by increasing public health programs in UKK (Upaya Kesehatan Kerja). Primary health care’s UKK programs include annually refreshing and introspective or self-assessment programs that can help the informal industry to implement occupational health and safety, develop UKK station, and UKK cadres couching. The implementation of occupational safety and health (OSH) and UKK is expected can decrease the prevalence of work-related accidents and health problems in the informal industrial sector.Conclusion: The UKK caders’ knowledge about the implementation of occupational health and safety and UKK is still poor. Annually refreshing program is so important to improve caders’ knowledge and understanding. The introspective programs showed that not many informal industries those have UKK station. The role of UKK programmer in primary health, i.e. general practitioners and nurses, and also the government have an important influence in developing, monitoring, and evaluating the implementation of occupational health and safety programs.